The consumption multiplier of government spending: The role of substitutability between government spending and leisure - Masataka Eguchi; Yuhki Hosoya; Mai Yamada (Osaka University, Institute of Social and Economic Research (ISER), 2023)
It has been empirically observed that consumption responds positively to government spending shock, however, existing models with intertemporally-optimizing households do not easily reconcile this stylized fact. This paper aims to address this discrepancy between models and data, focusing on the non-separable preferences with respect to consumption, leisure, and government spending. We derive conditions for a positive consumption multiplier under the general utility function and find that consumption can respond positively when leisure and government spending are substitutes. Examples of government spending that would have such an effect include care for children and the elderly, education spending, highway and public transportation.
Keywords: E62; E32; E60; 330; Fiscal multiplier; Non-separable preferences; Substitutability